A benchmarking study of Geant4 for Auger electrons emitted by medical radioisotopes. (August 2021) - Bakr, Samer; Kibédi, Tibor; Tee, Bryan; Bolst, David; Vos, Maarten; Alotiby, Mohammed; Desorgher, Laurent; Wright, Dennis Herbert; Mantero, Alfonso; Rosenfeld, Anatoly; Ivanchenko, Vladimir; Incerti, Sebastien; et al.
Abstract: Auger emitting radioisotopes are of great interest in targeted radiotherapy because, once internalised in the tumour cells, they can deliver dose locally to the radiation sensitive targets, while not affecting surrounding cells. Geant4 is a Monte Carlo code widely used to characterise the physics mechanism at the basis of targeted radiotherapy. In this work, we benchmarked the modelling of the emission of Auger electrons in Geant4 deriving from the decay of 123 I, 124 I, 125 I radionuclides against existing theoretical approaches. We also compared Geant4 against reference data in the case of 131 Cs, which is of interest for brachytherapy. In the case of 125 I and 131 Cs, the simulation results are compared to experimental measurements as well. Good agreement was found between Geant4 and the reference data. As far as we know, this is the first study aimed to benchmark against experimental measurements the emission of Auger electrons in Geant4 for radiotherapy applications. Highlights: Auger electrons can deliver dose locally to the radiation sensitive targets. The emission of Auger electrons in Geant4. The Auger electrons are alternative channel to X-ray fluorescence. Geant4 is extensively used in medical physics applications. Geant4 in terms of emission of Auger electrons.